Dislocation/Relocation: re-discovering, asserting & re-imagining identity in Yeoville - Olver, Candice (My University, 2010)
This thesis aims to explore the process of identity construction within the context of the urban environment of Johannesburg. This exploration aims to inform the design of a Social Centre that will facilitate the process of personal and communal identity construction within the suburb of Yeoville, Johannesburg. The intention is to re-design an existing community centre on a key public space in such a way that it will reactivate and add value to the public space in the suburb of Yeoville (and in turn facilitating the city of Johannesburg) and the expression of the identity of Yeoville and in the process provide a space in which people can explore their own identity and contribute to the identity of Johannesburg